The influence of carbohydrate and protein ingestion during recovery from prolonged exercise on subsequent endurance performance - Betts, J.; Williams, C.; Duffy, K.; Gunner, F. (Journal of Sports Sciences, 2007)
Ingesting carbohydrate plus protein following prolonged exercise may restore exercise capacity more effectively than ingestion of carbohydrate alone. The objective of the present study was to determine whether this potential benefit is a consequence of the protein fraction per se or simply due to the additional energy it provides. Six active males participated in three trials, each involving a 90-min treadmill run at 70 % maximal oxygen uptake (run 1) followed by a 4-h recovery. At 30-min intervals during recovery, participants ingested solutions containing: (1) 0.8 g carbohydrate/kg body mass (BM)·h plus 0.3 g/kg·h of whey protein isolate (CHO-PRO); (2) 0.8 g carbohydrate/kg BM·h (CHO); or (3) 1.1 g carbohydrate/kg BM·h (CHO-CHO). The latter two solutions matched the CHO-PRO solution for carbohydrate and for energy, respectively. Following recovery, participants ran to exhaustion at 70% maximal oxygen uptake (run 2). Exercise capacity during run 2 was greater following ingestion of CHO-PRO and CHO-CHO than following ingestion of CHO (P 0.05) with no significant difference between the CHO-PRO and CHO-CHO treatments. In conclusion, increasing the energy content of these recovery solutions extended run time to exhaustion, irrespective of whether the additional energy originated from sucrose or whey protein isolate.